Watching Indonesian sinetron: imagining communities around the television - Ida, Rachmah (Curtin University, 2006)
This thesis is about the everyday cultural practices of communal television viewing by urban kampung people. It challenges the institutional frameworks and constructs about the television audience. To achieve this, the thesis looks at the cultural context of the television set and its uses in urban kampung households and the neighbourhood system. Studies on urban kampung community in Indonesia so far have focused on the socio-economic and cultural practices of the people in relation to state ideological matters (e.g. Guinness, 1989; Sullivan, 1994; Brenner, 1998). This thesis is an attempt to extend the investigation about the cultural practices of the kampung community in relation to media use in the era of competitive private television in the early 2000s. As those kampung people have existentially engaged in fashioning their own lives neither as rural subjects nor urban/ity subjects, their narratives in responding to televised images and representations (of women in particular) shape the particularity of the cultural scene of these marginalized subjects. Taking up their social economic background and the particularities of socio-cultural circumstances of the kampung, this present study takes a close look into the day-to-day communal viewing practice of the kampung female viewers of the most-watched local program on Indonesian television, that is sinetron (television drama).Extending the argument of Ien Ang and others into the Indonesian context, the thesis concludes that the national television audience as a unified, atomistic and controllable entity, as is institutionally imagined, does not exist. Rather, watching television, particularly among the urban middle to lower class community, is a discursive practice overwhelmingly showing the diverse, particular, and unpredictable attitudes, which challenge the account of 'the audience' that characterises the industry, the state and, ironically, also the intellectual critical knowledge producers.